An algorithm for determining data forwarding strategy based on recommended trust value in MANET. (5th May 2020) - Xu, Jianbo; Feng, Shu; Liang, Wei; Ke, Jian; Meng, Xiangwei; Zhang, Ruili; Shou, Danping
In mobile ad hoc networks (MANET) with selfish nodes and malicious nodes, the network performance is seriously affected. We propose an algorithm based on the recommended trust value, i.e., collaborative computing trust model (CCTM) algorithm, to decide the data forwarding strategy. In the algorithm, the carrier node carrying the message collects recommended data of neighbour nodes adopts K-nearest neighbour (KNN) algorithm principle to filter the false recommended data and select K neighbour nodes as collaborative computing nodes to calculate the recommended trust value of neighbour nodes respectively, and then selects the neighbour node with the highest recommended trust value as the next hop node. The simulation experiments show that when the selfish and malicious nodes number is 10, CCTM is higher than Epidemic algorithm and MDT about 3% and 8% respectively in terms of transmission success rate; CCTM is higher than Epidemic about 14% and lower than MDT about 15% in terms of average transmission delay; CCTM is lower than MDT about 3% in terms of routing overhead. Overall, CCTM algorithm not only has better performance in terms of transmission success rate, delay and routing overhead, but also improves the security of data transmission.